What's new in Visual FoxPro 7.0 - Granor, Tamar E. (Hentzenwerke Pub., 2001)
What's new in Visual FoxPro 7.0? Lotsa stuff!!!!! Read All About It Here! Visual FoxPro 7.0 has been called the most revolutionary upgrade since 3.0. Whether you agree or not, there's a lot of new stuff in the latest to appear from the Fox labs in Redmond - and you won't find a better, more concise guide of what's new, and how to use it, than in this compendium put together by three of the finest Fox developers on the planet.